PELESTARIAN LINGKUNGAN DESA WISATA: PERAN KELOMPOK USAHA PERHUTANAN SOSIAL DI KAMPUNG DURIAN JEMBER - Holida, Muti'atu Nur Diana; Sukidin; Mardiyana, Lisana Oktavisanti (JURNAL KEPARIWISATAAN, 2025)
The establishment of Social Forestry Business Groups is a part of the social forestry program aimed at improving community welfare through forest-based economic activities. This study analyzes the role of the Wisata Rengganis Social Forestry Business Group in environmental conservation within the Kampung Durian Tourism Area, Pakis Village, Panti District, Jember Regency. Employing a qualitative method with a case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the Wisata Rengganis Social Forestry Business Group contributes to environmental conservation through three aspects of sustainable forest management: (1) community-based forest management involving residents and youth, (2) resource-based forest management through greening and soil conservation, and (3) good corporate governance, which includes having a clear organizational structure, information transparency, openness to community and visitors suggestions, and decision-making through deliberation.